The Posology of Oseltamivir in Infants With Influenza Infection Using a Population Pharmacokinetic Approach. Issue 3 (27th May 2014) - Kamal, M A; Acosta, E P; Kimberlin, D W; Gibiansky, L; Jester, P; Niranjan, V; Rath, B; Clinch, B; Sánchez, P J; Ampofo, K; Whitley, R; Rayner, C R
<x xml:space="preserve">Abstract</x> Infants are at increased risk for morbidity and mortality due to influenza. Until recently, few data were available with which to optimize oseltamivir dosing in this high‐risk population. Here, data for 133 infants were pooled from two prospective pharmacokinetic/pharmacodynamic safety studies to develop a population pharmacokinetic model. A three‐compartment model with allometric scaling of all clearance and volume parameters described the disposition of oseltamivir and its carboxylate metabolite (OC). Weight dependence, OC clearance, and volume of distribution increased linearly with age. Analyses showed no association between OC exposure and viral clearance, the development of resistance (phenotypic/genotypic), normalization of body temperature, or safety endpoints. Pharmacokinetic bridging showed that a 3 mg/kg dose yielded acceptable OC exposure and good tolerability while minimizing the risk of underexposure and resistance/treatment failure. These pharmacological analyses formed the basis of the US Food and Drug Administration's recent approval of oseltamivir treatment for infants with influenza aged as young as 2 weeks. Clinical Pharmacology & Therapeutics (2014); 96 3, 380–389. advance online publication 25 June 2014. doi:10.1038/clpt.2014.120